MENINGKATKAN KEMAMPUAN MENULIS TEKS CERITA PENDEK DENGAN MENGGUNAKAN MEDIA TEKS LAGU - Santoni, Tutun; Mansur, Maulana; Mahardika, Reka Yudha (IKIP Siliwangi, 2018)
This research aims to see the effect of using song text in improving the ability to write short story text in high school. Short story is included in the material in Indonesian lesson that is able to increase students' writing skill, but the fact that writing is still less a priority in school, one of them in writing short story because of their various obstacles in writing. The method used in this research is quantitative quasi-experiments, students of grade XI SMA Pasundan 3 Cimahi 2017/2018 which become population in research, which become sempel in research is student of class XI IPS 2 (experiment) which given treatment in the form of research method and class XI IPS 1 as a control class (control) that is not given treatment of research methods. Data collection techniques in this study in the form of preliminary and final tests. Based on hypothesis t test calculation, the result t / table ≤ t / arithmetic ≥ t / table, that is 1.67 <4.34> 2.39. The hypothesis of this research is the use of text media songs in an effort to improve writing short story text. Based on the results of data analysis, the research hypothesis can be proven true, seen from the increase in the average value in writing short stories. The average value of the original 53.3 increased to 78.3. This shows that the use of the song text media is effective in improving the ability to write short story text.